Young life and times survey, 2018 - Schubotz, Dirk (Northern Ireland Life and Times Survey, 2019)
The Young Life and Times Survey (YLT) originally began as a companion survey to the Northern Ireland Life and Times Survey (NILT) series. It surveyed young people aged 12-17 living in the households of adults interviewed for NILT, and YLT ran alongside it from 1998-2000. Following an evaluation in 2001, the YLT series recommenced in 2003 (see SN 4826) using a completely different methodology and independent of the adult NILT. This new YLT survey uses Child Benefit records as a sampling frame. The aims of the YLT series are to: monitor public attitudes towards social policy and political issues in Northern Ireland; provide a time series on attitudes to key social policy areas; facilitate academic social policy analysis; provide a freely available resource on public attitudes for the wider community of users in Northern Ireland; give a voice to young people. An open access time-series teaching dataset has been created from the 2003-2012 YLTs - see SN 7548. The Kids’ Life and Times (KLT) survey of P7 children (10-11 year olds) is also part of the same suite of surveys as YLT and NILT.